VD_FINDINFO HC / 2012 / 184 vom 8. Februar 2012 - VD Tribunal cantonal (2012)
DROIT EXCLUSIFPROPRIÉTÉ PAR ÉTAGES, PROPRIÉTÉ PAR ÉTAGES | 647d CC, 648 CC, 712a CC, 308 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH), 405 al. 1 CPC (CH)